Literary Works Empowering Social Movements: A Doll's House & Bumi Manusia Analysis in Norwegian-Indonesian Feminism - R. Hariyani Susanti (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2023)
This article explores the role that literature plays in social movements, particularly in the gender equality movement such as women’s autonomy in social settings. By comparing two literary works, A Doll’s House by Henrik Ibsen and Bumi Manusia by Pramoedya Ananta Toer, the article investigates the impact of literature on the first wave of the feminist movement in Norway in 1879 and the portrayal of women's conditions in Indonesia at the time. The research employed qualitative research methods such as content analysis and discourse analysis, as well as comparative analysis of the two literary works. The research found that A Doll’s House played a significant role in the Norwegian feminist movement and gave women confidence and the awareness that they were not merely puppets for men, but human beings whose voices needed to be heard. Similarly, Bumi Manusia showed resistance and awareness of the oppression faced by Indonesian women, highlighting the role of literature in promoting equality movements. These important literary works demonstrate the power of literature in documenting, retelling, and raising awareness of people's stories, ultimately reaching a larger audience.